A study of the efficiency of irrigation water application according to (a) the gravimetric, (b) the Penman, (c) the Thornthwaite and (d) the Pan evaporation bases as judged by green plant growth of maize - Pantazis, Vlassios (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc. Agric.) -- University of Stellenbosch, 1963.